2016
DOI: 10.1134/s1063782616040059
|View full text |Cite
|
Sign up to set email alerts
|

Polytype inclusions and polytype stability in silicon-carbide crystals

Abstract: On the basis of both published data and our own experimental data we consider the main aspects of the problem related to ensuring polytype stability for ingots of grown 4H and 6H silicon-carbide compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 65 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…D.D. Avrov et al reported that nitrogen actively prevents three-dimensional growth by decreasing the height of microsteps at the crystallization surface and the mechanism of surface-catalytic action of nitogen leds to layer-by-layer growth [10]. However, in the heavily nitrogen-doped 4H-SiC crystals grown, the higher micro steps are generated and that bring about the transformation from threading screw dislocations to basal plane disloations [11].…”
Section: Resultsmentioning
confidence: 99%
“…D.D. Avrov et al reported that nitrogen actively prevents three-dimensional growth by decreasing the height of microsteps at the crystallization surface and the mechanism of surface-catalytic action of nitogen leds to layer-by-layer growth [10]. However, in the heavily nitrogen-doped 4H-SiC crystals grown, the higher micro steps are generated and that bring about the transformation from threading screw dislocations to basal plane disloations [11].…”
Section: Resultsmentioning
confidence: 99%
“…Different polytypes of a given material can be formed under identical temperature, pressure, and concentration conditions. For polytypes, the "syntactic coalescence" of different polytypes, i.e., the simultaneous coexistence of more than one polytype within a crystal or an epitaxial layer [30][31][32][33][34][35][36][37], or polytype inclusion formation after completing a technological process step [37][38][39][40][41][42][43][44][45][46][47][48] or device operation [48][49][50][51] is a common effect. On the other hand, because of the different physical properties of the different polytypes, silicon carbide represents a family of semiconductor materials.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies on the bulk energy and surface energy of the common SiC polytype show different stability orders, depending on the calculation methods and parameters. However, all these studies show a small energy difference between 3C, 6H, and 4H SiC. Therefore, during the synthesis process, the SiC polytype could be changed by a small disorder of the crystal structure.…”
Section: Introductionmentioning
confidence: 99%